(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
India has witnessed a rapid growth in digital technologies over the past decade, with a large percentage of the population now accessing the internet through mobile devices. The trend of using digital mode of finance is now gradually shifting towards the vision of a purely virtual banking experience. Undertaking financial services virtually has now become a common phenomenon and the financial habits and consumption pattern of financial services has now taken a paradigm shift from traditional to virtual. Digital awareness has become an increasingly important affair, particularly between Generation-Y and Generation-Z. Although both generations have grown up with digital technologies at their fingertips, there are significant differences in their digital awareness and how they use digital financial services. This research has explored the difference in level of digital financial awareness between Gen-Y and Gen-Z. Their consumption pattern and financial habits have been understood through collection of primary data through a structured questionnaire. The awareness level of the respondents of Gen-Y and Gen-Z has been compared based on their gender and age. For analyzing the data, frequency and percentage has been evaluated of the demographic profile and other variables. Hypothesis has been tested through the use of t-test and ANOVA applied through SPSS 20.